Sound Signal Analysis Using FIR Filters for Musical Fountain Operation - Jasim, Ali M.; Mahmood, Jawad R.; Ali, Ramzy S. (Basrah Journal for Engineering Sciences, 2016)
In digital signal processing (DSP), FIR digital filter is very important device to deal with particular frequencies of a certain signal to be appropriate for some applications such as communications, sound equalizers, etc. In this paper, FIR filters are adopted to decompose the original sound signal into four signals. Each one is created by one FIR filter and each filter represents a narrow band of frequencies. The filter output is used to drive a certain variable speed drive (VSD) to control the speed of a water pump and light intensity of a colored lamp. This filter output signal is applied to the analog control voltage terminals of the VSD unit to control the frequency and magnitude of the voltage supplied to the lamp and pump. Thus, the heads of the water jets and the light intensity are controlled according to the analog control signals which are created by the FIR filters (The VSD is used to map the filter output into light intensity and water head by controlling the supplied voltage of them). The goal of this study is to design and simulate four sound harmonics bands produced by FIR filters to drive four VSDs which are simulated using V/F ratio constant method for musical fountain operation.